Perkembangan Ekspor dan Impor Menurut Sektor di Provinsi Sumatera Utara Tahun 2018-2022 - Ellen Angelina Nainggolan (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study explores the development of exports and imports in North Sumatra Province over the period 2018-2022. The primary focus is on analyzing the trends in export and import values and their impact on the trade balance and trade ratio within the region. The data collected shows fluctuations in export and import values from year to year, with a notable increase in 2021 and 2022. This indicates a shift in trade dynamics influenced by various factors, including global economic conditions and trade policies implemented. The trade balance of North Sumatra Province during this period generally reflects a surplus, indicating that export performance remained higher than imports. Furthermore, the trade ratio demonstrates an improvement in the export competitiveness of North Sumatra, which positively contributes to the regional economy. This study provides a comprehensive overview of North Sumatra’s international trade patterns and highlights the importance of strategic trade policy management to support sustainable economic growth.